The potential health impact of restricting less-healthy food and beverage advertising on UK television between 05.30 and 21.00 hours: a modelling study - Mytton, OT; Boyland, E; Adams, J; Collins, B; O'Connell, M; Russell, SJ; Smith, K; Stroud, R; Viner, RM; Cobiac, LJ (Public Library of Science, 2020)
Background Restrictions on the advertising of less-healthy foods and beverages is seen as one measure to tackle childhood obesity and is under active consideration by the UK government. Whilst evidence increasingly links this advertising to excess calorie intake, understanding of the potential impact of advertising restrictions on population health is limited.